Analisis Pengaruh Elektroda E309-16 Pada Sambungan Baja Carbon Aisi 1045 Dan Stainless Steel 304 Dengan Menggunakan Pengelasan Smaw - Haryanto, Budi; Tuparjono, Tuparjono; Darta, Yuli (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The bimetallic welding process is a welding process that connects two different types of metal. This study aims to determine the effect of the E309-16 electrode on the connection of two materials using smaw welding on tensile strength. The materials used were carbon steel AISI 1045 and stainless steel 304. This study used an experimental method with a penetration and filling welding process with a 60° V seam using an E309-16 electrode. The shape of the specimens in this study used the ASTM E8 standard. From the results of the tensile test research conducted, the E309-16 electrode has an influence on the bimetallic welding process on AISI 1045 carbon steel and 304 stainless steelwith a resulting tensile strength of 58.01 Kg/mm – 68.48 Kg/mm, yield strength that is produced by 35.97 Kg/mm – 37.12 Kg/mm, the resulting strain value was 12.50% - 43.00% and was able to withstand a given tensile load of 6450 Kg – 7900 Kg. and the bimetallic welding process using the E309-16 electrode has a more binding effect on the 304 stainless steel material, this is evidenced by the broken specimens in the weld area and the lower carbon content of 304 stainless steel with a carbon content of 0.042% compared to AISI steel material 1045 which has a carbon content of 0.42%.